Love and Hate: Existentialism and Psychoanalysis – A Personal Perspective (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
In this presentation I will be attempting to expresses some views and a few ideas on dualism, drawing from personal experience and practice. Much of the existential-phenomenological literature critiques classical psychoanalysis. However there is a strong emerging school in contemporary psychoanalysis that arguably challenges the traditional duality and offers significant points of convergence.
Keywords: existentialism; psychoanalysis; duality; uncertainty; phenomenology; trauma; postpsychiatry; childhood.